TECHNOLOGICAL INVENTIONS TO FIGHT AGAINST COVID-19: A REVIEW - Pulkit Jain (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
COVID-19 might be devastatingly affecting our enterprises, public activities and individual prepping norms and principles, yet it is likewise inciting an overflowing of innovativeness in different fields. Science and Technology is playing a pivotal role in an effort to tackle this deadly pandemic. The objective of this paper is to carry out a review on the latest technological inventions that have been carried out by researchers, medical as well as top engineering institutions, universities and organizations worldwide to fight against coronavirus. Firstly, six different digital technologies are discussed as how they are helping people in the battle against COVID-19. Then the paper gives a detailed overview of numerous technological inventions like artificial hygienic hand: hands-free door openers, snood-type mask, UV disinfection towers, smart helmets and contact free sanitization cabinets etc. At the end, the conclusion talks give a solid conviction these latest technologies like AI, NLP, Block-Chain, 3D printing, AR/VR will play a pivotal role in helping people to fight against this COVID-19.